Peningkatan Kompetensi Bahasa Inggris dan Literasi Keuangan Siswa SMP Negeri Upuhupun melalui Program English for Daily Life and Simple Accounting - Parjolo Aritonang; Wenssy Steva Nussy; Stella Rose Que; Punggulina Andawaty Tiven (Abdimas Indonesian Journal, 2026)
This service aims to improve practical English competence and financial literacy of students of Upuupung State Junior High School, Southwest Maluku, a disadvantaged and remote area with limited access to education. The methods used are participatory learning and experiential learning through two modules: English for Daily Life (greeting, everyday vocabulary, family and village descriptions, simple transactions) and Simple Accounting and Financial Literacy (introduction to money, distinguishing needs and wants, saving, simple financial record-keeping). The activity was attended by 40 students for one month, culminating in the "Upuhupun Mini Market Day" simulation that integrated both skills. The results of the activity showed an increase in students' confidence in communicating in English, understanding the concept of money management, and the practical ability to carry out simple buying and selling transactions. The outputs produced include teacher guide modules, reading corners containing English storybooks and financial literacy, and learning media. The obstacles faced are limited time, facilities, and weather conditions. The conclusion of this service is that contextual, integrative, and fun approaches have proven to be effective in empowering students in the 3T area. Sustainability recommendations include the adoption of role-play methods and simple projects by teachers, as well as the implementation of Market Day as an annual school activity.